Dining at casual-typed restaurant: descriptive findings from Klang Valley, Malaysia - Ahmad, Faridah; Ungku Zainal Abidin, Ungku Fatimah; Ghazali, Hazrina; Othman, Mohhidin (2015)
This study aimed to identify the pattern of consumption among casual dining restaurant customers in Klang Valley area, Malaysia. To achieve the objective, 800 questionnaires were distributed. Only 682 responses were accepted for further analysis. Data analysis was performed using Statistical Package for Social Science (SPSS) version 21. The information of consumption at casual dining restaurant namely (1) frequency of visiting to casual dining restaurant, (2) source of information influenced restaurant selection, (3) reasons of dining out at casual dining restaurant, and (4) average of spending at casual dining restaurant are gathered through this study. The results obtained provide valuable information for practitioners in planning operations and formulate strategy based on consumption pattern in order to attract new customers, retain the existing customers and capture customer’s desire instead of only focusing on earning maximum profits.